KUALITAS INFORMASI KEUANGAN DIGITAL, KEPERCAYAAN DAN MINAT INVESTASI GENERASI Z DI ERA FINTECH - Evie Sukma; Lily Ulfia (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study explores the role of digital financial information quality in fostering trust and investment intention among Generation Z in Kendari City during the fintech era. Employing a qualitative approach with an ethnographic case study design conducted over a three-month period (January–March 2025), the study involved 12 participants aged 18–27 years through semi-structured interviews and observations of online investment communities. Inductive thematic analysis supported by NVivo 12 identified four major themes: (1) perceptions of the quality of digital financial information, (2) the dynamics of trust formation toward fintech platforms, (3) the drivers and barriers influencing investment intention, and (4) the role of the digital social ecosystem in investment decision-making. This study contributes theoretically by providing insights from a medium-sized city in Eastern Indonesia, where socioeconomic conditions and digital infrastructure differ from those of major metropolitan areas. It also offers practical recommendations for fintech developers, regulators, and educational institutions to support the advancement of national financial inclusion.